Soil Behavior and Liquefation Potential During Earthquake in Kulonprogo, Yogyakarta, Indonesia - Qodri, Muhammad Fatih; Anggorowati, Veronica Diana Anis (UIR PRESS, 2026)
Indonesia is a country that is prone to natural disasters such as earthquakes and landslides, especially in areas along the Pacific Ring of Fire. The region of Kulonprogo in Yogyakarta, has a unique geotechnical profile that poses particular challenges in assessing soil behavior under seismic events. This study investigates the liquefaction potential and dynamic soil behavior in Kulonprogo during an earthquake scenario, using a combination of Deterministic Seismic Hazard Analysis (DSHA) and Next Generation Attenuation (NGA) models. These approaches allow for precise evaluation of seismic hazards by analyzing ground motion predictions based on past events and site conditions. Using data from the 2006 Yogyakarta earthquake and the Pacific Earthquake Engineering Research (PEER) database, the model the soil response and assessing potential liquefaction are conduted. Kulonprogo's soil primarily consists of loose sands and silts, which are prone to liquefaction, especially under strong ground shaking. Key findings show significant variations in soil behavior, with peak ground acceleration values reaching approximately 0.1 g. The analysis indicates that maximum surface pressure decreases with depth, with values around 0.09 kPa at the surface, dropping to nearly 0 kPa at 30 meters. Maximum acceleration profiles show surface accelerations peaking at 2.2 g, highlighting the susceptibility of shallow soil layers to liquefaction. Relative displacement profiles indicate notable deformation, with displacements reaching about 0.03 m at the surface, decreasing significantly with depth. These results underscore the importance of understanding local geological conditions for accurate seismic hazard assessments and structural safety evaluations. The findings contribute to the development of targeted mitigation strategies and inform earthquake-resistant design practices, ultimately enhancing disaster resilience in Kulonprogo and similar seismically active regions in Indonesia.